The four mechanisms of dental resorption initiation - Alberto Consolaro (Dental Press Editora, 2013)
The aim of this study is to present a classification with a clinical application for root resorption, so that diagnosis will be more objective and immediately linked to the source of the problem, leading the clinician to automatically develop the likely treatment plan with a precise prognosis. With this purpose, we suggest putting together all diagnosed dental resorptions into one of these four criteria: 1) Root resorption caused by cementoblast cell death, with preservation of the Malassez epithelial rests. 2) Root resorption by cementoblasts and Malassez epithelial rests death. 3) Dental resorption by odontoblasts cell death with preservation of pulp vitality. 4) Dental resorption by direct exposure of dentin to gingival connective tissue at the cementoenamel junction gaps.